Dynamic response of woody vegetation on fencing protection in semi-arid areas; Case study: Pilot exclosure on the Firmihin Plateau, Socotra Island - Habrova, Hana; Pavlis, Jindrich (Saudi journal of biological sciences, 2017)
Woody vegetation dynamics and Dracaena cinnabari regeneration have been studied for five years in the conditions of Socotra Island. Woody plants were measured regularly inside and outside the exclosure area, and the growth and survival of D. cinnabari seedlings were observed. In the exclosure of about 1000 m2 a total of 49 species were identified, including 23 endemics, growing in the average density of 3.82 specimens per m2. The fenced area was overgrown relatively rapidly by dense grass cover - reaching approx. 2.7 t/ha. Species growth dynamics inside and outside the exclosure shows that grazing had a marked impact, leading to the elimination of trees and shrubs. All grazed species grew noticeably in the exclosure, in the average of 50 cm in 5 years. D. cinnabari as the dominant flagship species of Socotra has been studied with regards to regeneration dynamics. Observations indicate that probability of its seedlings survival increases with their age. No seedlings germinated from the seeds sown in the experiment, however, outplanted seedlings performed relatively well. Field observations show that D. cinnabari seed germination is triggered when the seed reaches a protected micro-habitat with a developed humus layer and high relative humidity in the soil lasts for at least two days.
Keywords: Dracaena; Soqotra; Grazing; Regeneration